Análise da ativação e relevância funcional de vias sinalizadoras celulares durante a infecção pelo Vaccinia virus Belo Horizonte - Jonas Dutra Albarnaz (2010)
During infection, viruses rely on cell metabolism and, at the same time, evade from host antiviral responses, to guarantee their efficient replication and dissemination. In spite of poxviruses encoding a plethora of immune evasion proteins, they also manipulate intracellular signaling pathways to create an environment propitious to virus replication. In Brazil, several strains of Vaccinia virus (VACV) have been isolated from outbreaks involving rodents, cows and humans, characterizing them as emerging zoonoses. As these Brazilian VACV strains, isolated from natural infections, constitute a useful tool to investigate virus-host interaction, the aim of this work was to analyze activation and functional relevance of cellular signaling pathways during VACV Belo Horizonte (VBH) infection, in comparison to VACV Western Reserve (WR). VBH was isolated during a mousepox outbreak in UFMG’s animal facility. During infection of A31 cells (3T3 fibroblasts derived from Balb/C mice), VBH and VACV-WR temporally regulate the activation of MAPK MEK/ERK, JNK and p38, and of PI3K/Akt in similar fashion. However, pharmacological inhibition of MEK/ERK (UO126), PI3K/Akt (LY294002) and JNK (JNK inhibitor VIII) did not affect significantly VBH replication (inhibition ≤ 50%), in contrast to VACV-WR. Inhibition of p38 (SB202190) reduced VBH progeny in 90%, but did not for VACV-WR. Genistein (protein tyrosine kinase inhibitor) and two known unspecific drugs (SP600125 e Akt inhibitor IV) inhibited equally VBH and VACV-WR replication, indicating their potential antiviral activities. In presence of LY294002, VBH replication and early/late protein synthesis were delayed, but not inhibited like VACV-WR. VBH morphogenesis also proceeded normally in presence of LY294002. Therefore, in contrast to VACV-WR, VBH infected cells underwent apoptosis even in the absence of PI3K/Akt inhibition. In spite of that, four viral genes (B13R, E3L, F1L e N1L) directly involved in apoptosis inhibition did not present polymorphisms in VBH. Both viruses replicated in murine macrophages, but VBH induced cytokine gene expression 2 log10 lesser than VACV-WR. In conclusion, these data indicate that VBH and VACV-WR, though closely related genetically, display biologic differences that certainly influence pathogenesis of these VACV strains in vivo.